The Isis Bibliography from Its Origins to the Present Day: One Hundred Years of Evolution of a Classification System - Weldon, Stephen (Circumscribere International Journal for the History of Science, 2009)
The article surveys the evolution of the Isis bibliographical classification systems over the past century. Begun in 1913 by George Sarton, the Isis Bibliography is continued to this day under the auspices of the History of Science Society. The classification systems have developed and changed gradually over the years, the most recent change being in 2002 when the author took charge of the publication as bibliographer. Changes in both scholarly interests and practice, on the one hand, and digital research technologies, on the other, have guided these most recent revisions. Each citation in the Isis bibliography receives two types of subject tagging, an ordered classification into a fixed category and indexing according to an expandable thesaurus. Precisely how these two types of subject tagging work now and how they came to be this way is the focus of this paper.